EMBANKMENTS ON SOFT GROUND INFLUENCE ON CONSOLIDATION OF VARYING THE A-OCR RELATIONSHIP - HARYANI, SRI
EMBANKMENT ON SOFT GROUND : INFLUENCE ON CONSOLIDATION OF VARYING THE A-OCR RELATIONSHIP, Sri Harianti, 1993, Program Sistem dan Teknik Jalan Raya, Program Pascasarjana, Institut Teknologi Bandung. It is required to predict the magnitude of excess pore water pressure and settlement in soft clays, and their time rates in order to evaluate the stability of overlying embankments. SKEMPTON (1954) derived a mathematical formula to predict the magnitude of excess pore water pressure, as a function of changes in vertical and isotropic stresses using pore pressure parameter A to express the influence of these changes. The parameter A is not constant; it must be determined for each soil and stress path. SKEMPTON (1954) proposed a relationship between A and overconsolidation ratio (OCR) at failure condition. Several variations of this relationship have been developed in order to examine the influence of A at pre-failure condition as a function of overconsolidation. A computer program to consider two-dimensional consolidation of stratified soft clays under embankment loading using Terzaghi-Rendulic and non-linear theories with A at failure condition were developed in previous studies. The KON2D ANT program was extended to include the options for A as a function of OCR in a pre-failure condition. The influence of A as function of OCR on excess pore water pressure and settlement were analyzed by using several data from well-documented case histories, i.e. Muar Flats (Malaysia), Juru (Malaysia), and Tickton (UK). The results showed that for these lighty overconsolidated clays, the influence of A on excess pore water pressure and settlement is not significant. The non-linear analysis was also applied to the trial embankment at Padalarang-Cileunyi Highway , the results then being compared with those from application of the Terzaghi-Rendulic analysis. In some histories the Terzaghi-Rendulic and non-linear theories provided similar results, while in others the non-linear provided better results. The influence of preconsolidation pressure value was analyzed for this location, and it was found that the magnitude and rate of settlement was sensitive to variation in preconsolidation pressure.